2012
DOI: 10.2166/wst.2011.844
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term fouling characteristics of reverse osmosis membrane at full scale leachate treatment plant

Abstract: This research is focused on characterizing the foulants on a reverse osmosis (RO) membrane taken from a full-scale leachate treatment plant in Thailand. The system consists of a physico-chemical pre-treatment unit and RO system and has been in operation for 2 years. Ferric chloride (FeCl(3)) was added to the open-jet sedimentation tank at 2.0-2.5 g/l dosage for chemical coagulation. The supernatant from the sedimentation tank was polished using a pressurized sand filter prior to entering the RO system. The RO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In previous membrane autopsy studies, it was reported that the fouling layers formed on membrane surfaces were heterogeneous and significantly dependent on the flow direction of the membrane element [9,13,25]. Generally, the deposition of particles, organic, and/or colloidal contaminants is usually on the lead port of each element and the first elements in each pressure vessel.…”
Section: Evidence Of Organic Foulingmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous membrane autopsy studies, it was reported that the fouling layers formed on membrane surfaces were heterogeneous and significantly dependent on the flow direction of the membrane element [9,13,25]. Generally, the deposition of particles, organic, and/or colloidal contaminants is usually on the lead port of each element and the first elements in each pressure vessel.…”
Section: Evidence Of Organic Foulingmentioning
confidence: 99%
“…Previous studies have demonstrated that desalination plants using brackish groundwater usually suffer from the accumulation or precipitation of inorganic salts, which mostly contain soluble multivalent ions such as calcium, aluminum, and sulfate ions [25,31]. Moreover, silica fouling also frequently occurred in groundwater desalination plants [32].…”
Section: Analysis Of Inorganic Foulantsmentioning
confidence: 99%
“…Raw leachate from young landfills contains most of organic substances in biodegradable form thus can be easily treated by biological processes. For old landfills, most of the leached organic compounds are hardly or non-biodegradable forms and they should be treated by physico-chemical processes or a combination of biological and physico-chemical pro-cesses [7]. On the other hand, the use of membrane technologies allows stable quality of the permeate that can be locally reused or discharged in water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, EDI device contains many semi-permeable ion exchange membranes, which may result in some membrane-associated problems such as concentration polarization and metal ions precipitation [10,16,17]. In our previous work, a novel membrane-free electrodeionization (MFEDI) process, combining the advantages of MBIE and EDI, was investigated and tested successfully for HPW production [18][19][20].…”
Section: Introductionmentioning
confidence: 99%